Real-world, very long-term follow up survival of incident patients with pulmonary hypertension. (14th October 2021) - Ferreira, C; Festas, T; Alves, P; Freitas, A; Almeida, J P; Martinho, S; Goncalves, V; Castro, G; Baptista, R; Goncalves, L
Abstract: Background: Pulmonary hypertension (PH) is a clinical syndrome characterized by an increase in pulmonary artery pressure. Among the five groups of PH, pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) stand out due to their ominous prognosis without specific treatment. However, very long-term outcomes data are scarce. Purpose: We aimed to assess the very long-term survival of PAH and CTEPH patients followed in a Portuguese PH referral center. Methods: Between January 2009 and January of 2020, all incident PH cases were consecutively enrolled in a prospective cohort study. A total of 177 patients were followed up for a median of 5.0 [interquartile range 2.3–8.7] years. Kaplan-Meier survival analysis was used to estimate 1-, 5- and 9-year survival and multivariate regression was used to predict independent prognostic factors. Results: Mean age was 49±20 years with a clear female preponderance (67%). The most common PH subgroups were congenital heart disease (PAH-CHD) (n=62; 35%), followed by CTEPH (n=52; 29, 4%), connective tissue disease (PAH-CTD) (n=31; 17.5%), idiopathic/hereditary PAH (I/HPAH (n=22; 12.4%) and portopulmonary hypertension (PoPH) (n=8; 4.5%) (Table 1). PAH-specific drugs were used in 91% of the patients, dual combination therapy in 47.5%, and triple combination in 12.4%. The remaining 9% successfully received non-pharmacological treatment, namely cardiac surgery in PAH-CHD (n=7) and endarterectomy or angioplasty in CTEPH (n=9). Survival rates at 1-, 5- and 9-years were 97%, 80% and 66%, respectively. Age (hazard ratio [HR] 1.02; 95% CI 1.01–1.04; P=0.049), BNP [HR 2.04 (1.16–3.60); P=0.01], admission for decompensation of heart failure (HF) [HR 3.15 (1.71–5.83); P<0.001] and PH type [P=0.01] were predictors of all-cause mortality. PAH-CHD had the better long-term survival (9-year survival of 83%), whereas PAH-CTD and PoPH were associated with a worse prognosis (9-year survival of 24% and 28%, respectively) (Figure 1). Regarding admissions for decompensated right HF, BNP was an independent predictor [HR 3.39 (2.12– 5.43); P<0.001] and no difference was found between PH etiologies. Conclusions: In this cohort of incident PH patients, the overall 9-year survival rate was 66%. PAH-CHD patients had better overall prognosis, while patients with PAH-CTD and PoPH had the worst prognosis. Additionally, older age, higher BNP and admission for HF were associated with higher mortality. Funding Acknowledgement: Type of funding sources: None.